The Interaction with the Dramatic Text in Raúl Serrano’s Acting Technique - Zucchi, Mariano Nicolás (2024)
Introduction: It has been observed that interpreting a dramatic text poses a challenge for many acting students. This paper questions the impact that acting techniques may have on this process. Objective: Embedded in a line of research that studies discursive practices in theatrical pedagogy (Zucchi, 2017, 2023), this work examines how Argentine director Raúl Serrano (2004) proposes to approach dramatic literature. The article seeks to demonstrate that the technique presents a series of methodological issues that render it inconsistent and impractical for interpreting dramatic texts. Methods: To do so, discourse analysis is employed, particularly from the perspective of the dialogical approach to argumentation and polyphony (García Negroni, 2023). Conclusions: The encountered difficulties are explained as a consequence of the meaning and dramatic text conceptions implied in this pedagogical approach to acting.